An unclocked analog-to-digital converter - Siek, Liter (2021)
An unclocked A/D technique using a serial chain of comparators in its speed limiting path is described. The design fabricated in 2 μm double-metal single-polysilicon p-well CMOS technology occupies an area of 1.67 mm×1.67 mm, produces an 8-bit conversion in<1 μs and consumes a power of 40 mW.